Pengaruh Satra Musik Arab Modern pada Lagu Sayyidi Ar-Rais karya Hama Meshary Hamdana - Zahrotul Mukaromah; Rika Astari; Salma Nuraeni; Febriani Indah Wulandari (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
The study purposes to provide an explanation of the influence of modern Arabic music literature on Arabic music. From this influence can present a song entitled